Respuestas

  • Usuario de Brainly
2013-06-03T23:19:08+02:00
*3x-2+7x=7-1 
10x = 7-1+2 
10x = 8
x = 8/10 = 0.8

*34=3x-6+2x
34+6 = 5x
x = 40/5 = 8

*6(7-x)=8(6-x)
42-6x = 48-8x
-6x+8x = 48-42
2x = 6
x = 6/2 = 3

*(x+2)·3=(13-x)·4+3
3x+6 = 52-4x+3
7x = 49
x = 49/7 = 7

*3(1-2x)+12=10-2(x-3)
3-6x+12 = 10-2x-(-6)
3-6x+12 = 10-2x+6
15-16 = -2x+6x
-1 = 4x
x = -1/4 = -0.25

*4(x-6)=12-(x-3)
4x-24 = 12-x+3
5x = 39
x = 39/5 = 7.8

*
-2(x+3)-4=18+4x
-2x-6-4 = 18+4x
-6x = 28
x = 28/-6 = -4.67 aprox.

saludos